(untitled) - Halliday, David (Hoboken, NJ, 2008)
No other book on the market today can match the 30-year success of Halliday, Resnick and Walker's "Fundamentals of Physics"! In a breezy, easy-to-understand style the book offers a solid understanding of fundamental physics concepts, and helps readers apply this conceptual understanding to quantitative problem solving. This book offers a unique combination of authoritative content and stimulating applications.
Keywords: Physics,Vật lý; Textbooks,Sách giáo khoa